7y-9=8y-1

Simple and best practice solution for 7y-9=8y-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7y-9=8y-1 equation:


Simplifying
7y + -9 = 8y + -1

Reorder the terms:
-9 + 7y = 8y + -1

Reorder the terms:
-9 + 7y = -1 + 8y

Solving
-9 + 7y = -1 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
-9 + 7y + -8y = -1 + 8y + -8y

Combine like terms: 7y + -8y = -1y
-9 + -1y = -1 + 8y + -8y

Combine like terms: 8y + -8y = 0
-9 + -1y = -1 + 0
-9 + -1y = -1

Add '9' to each side of the equation.
-9 + 9 + -1y = -1 + 9

Combine like terms: -9 + 9 = 0
0 + -1y = -1 + 9
-1y = -1 + 9

Combine like terms: -1 + 9 = 8
-1y = 8

Divide each side by '-1'.
y = -8

Simplifying
y = -8

See similar equations:

| -2(r+6)=-37 | | 2-2n=n+64 | | 0.33=6 | | 2x^2-10x=6 | | 10x-3=-17 | | (3k-7)/(5)=16 | | 49+1-4c=39c-2 | | 2k+k+4= | | [t+5]+3=12 | | 7-2x=0 | | 6x+8=4x+50 | | 3x+8=8+2x+x | | 729=x^3 | | 4(d-20)=1 | | 245=-7a | | (36-5x)+(36-5x)+4x+4x=x | | 3x+28=7(x+4)-4x | | 2(6+3)=18-3(16-3d) | | 6+12=16 | | x+17=36-x | | x=20-0.5y | | 5=1-2n+5 | | 4(d-5)=1 | | 5m-14=8m+4 | | 2.5x-(-8.2)=26.7 | | -8n+4(1+5)=6n-14 | | -11(x+9)=99 | | 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 |

Equations solver categories